2008
DOI: 10.2134/agronj2008.0075
|View full text |Cite
|
Sign up to set email alerts
|

Crop Response to Rotation and Tillage in Peanut‐Based Cropping Systems

Abstract: Production of peanut (Arachis hypogaea L.) in reduced tillage systems has increased in the United States during the past decade. However, interactions of tillage system and crop rotation have not been thoroughly investigated for large-seeded, Virginia market type peanut. Research was conducted at two locations in North Carolina during 1999 to 2006 to compare yield of corn (Zea mays L.), cotton (Gossypium hirsutum L.), and peanut in diff erent rotations planted in conventional and reduced tillage. Crop rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…However, when pooled across tillage systems and trials, peanut yield with the diking treatment was 3480 lb/acre compared with 3600 lb/ acre without the diking treatment (Table 3). Variability in peanut response to strip tillage compared with conventional tillage has been noted previously at this location (Jordan et al, 2008), and Sorensen et al (2010) reported no yield difference when comparing diking with a no-diking control.…”
Section: Cotton and Peanut Responses To Diking In Conventional And Resupporting
confidence: 67%
See 1 more Smart Citation
“…However, when pooled across tillage systems and trials, peanut yield with the diking treatment was 3480 lb/acre compared with 3600 lb/ acre without the diking treatment (Table 3). Variability in peanut response to strip tillage compared with conventional tillage has been noted previously at this location (Jordan et al, 2008), and Sorensen et al (2010) reported no yield difference when comparing diking with a no-diking control.…”
Section: Cotton and Peanut Responses To Diking In Conventional And Resupporting
confidence: 67%
“…Lint yield, pooled across trials, was 870 lb/acre for the diking treatment and 840 lb/acre for the no‐diking treatment (Table 3). Previous research indicates that cotton response to reduced tillage is influenced by soil characteristics and seasonal precipitation (Buman et al, 2005; Jordan et al, 2008; Bauer et al, 2010). The response of cotton yield to diking also has been variable (Nuti et al, 2009; Sorensen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments initiated in 1999 (Lewiston‐Woodville) and 2000 (Rocky Mount) included factors other than the comparison of peanut in stale seedbeds versus stubble from the previous crop as reported in this article (8,9,10). The size of whole plot units allowed comparison of cultivars, fumigation with metam sodium, and inoculation with Bradyrhizobium with independent and appropriate controls for each factor (8,9,10). The treatments discussed in this article are unique in that peanut response to stale seedbed and strip tillage into crop stubble are included.…”
Section: Locations and Treatment Factorsmentioning
confidence: 99%
“…Peanut pods and vines were allowed to air dry for 4 to 7 days after digging and before harvest and final peanut yield was adjusted to 8% moisture. Yield of crops other than peanut are reported elsewhere for the long‐term experiments initiated in 1999 at Lewiston‐Woodville and 2000 at Rocky Mount (8,9,10). Yield of corn and grain sorghum was not recorded the year prior to planting peanut in the experiments initiated in 2004 and 2005 at Lewiston‐Woodville.…”
Section: Data Collection and Statistical Analysesmentioning
confidence: 99%
“…Jordan et al. () found that corn ( Zea mays L.) and seed cotton ( Gossypium hirsutum L.) yields in North Carolina were not affected by rotations with peanut under conventional and conservation tillage. In Alabama, removal of peanut residues after harvest did not affect seed cotton yields or rye ( Secale cereale L.) biomass accumulation (Balkcom, Wood, Adams, & Meso, ; Meso et al., ).…”
Section: Introductionmentioning
confidence: 99%